“Or whatever you be”: Crossdressing, Sex, and Gender Labour in John Lyly’s Gallathea - Chess, Simone (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2015)
This article explores sociologist Jane Ward’s gender and sexuality theory: the notion of “gender labour,” in which a cisgender (not crossdressed or trans) partner participates in co-creating his or her partner’s queer gender. While work on gender labour thus far has focused on contemporary subjects, this article demonstrates the ways in which the concept can be generatively applied to an early modern context. The concept is pushed to its extremes in John Lyly’s Gallathea, in which the two genderqueer crossdressers, Gallathea and Phillida, each thinking that the other is male, create and enact romantic love scenes that involve gender play and a co-created divestment from biological sex.